WEB-BASED DATA VISUALISATION FOR MEMBERS OF MASJID JAMEK BOTA KANAN - Mazlan, Mohd Iqbar (IRC, 2019)
This project is aimed at developing web-based system with data visualization for members of Masjid Jamek Bota Kanan. Some features of this system will be keeping and organize personal data of members of Masjid Jamek Bota Kanan, use data collected and analyze to do decision making for financial aid. To explain a little bit further, this system is eager to ensure Masjid Jamek Bota Kanan have a proper place to store personal data regarding it members. As before this system been created, Masjid Jamek Bota Kanan is still using traditional ways of data keeping which is by using pen and paper. Besides that, data visualization will help organization of Masjid Jamek Bota Kanan to identify and ease decision making to help those of their members who in need of financial help.